STRUKTUR KOMUNITAS ANNELIDA SEBAGAI BIOINDIKATOR PENCEMARAN SUNGAI ANCAR KOTA MATARAM - Iwan Doddy Dharmawibawa (Bioscientist : Jurnal Ilmiah Biologi, 2019)
Ancar River is a river that is used by many residents for various activities, such as agricultural activities, fisheries, and planting water spinach. In addition to these activities, the Ancar River is also used as a place for domestic waste disposal and disposal of the tofu waste industry so that it can have a negative impact on water resources, including causing a decrease in water quality. The Annelida response to environmental changes can be used to see the effect of various activities, such as the impact of industrial activities, agriculture, and land use. This study aims to assess the community structure of Annelida as bioindicators of the waters against the content of polluted material found in the Ancar River. This research is descriptive explorative, using quantitative and qualitative approaches. This study uses the "Sampling Purposive" method, which is the determination of the observation station based on the use of land around the Ancar River environment. Each sampling station is carried out in 3 points, namely left, center and right of the river. Annelida obtained in the Ancar River consist of two classes namely Oligochaeta and Hirudinea. Oligochaeta class consists of Tubifex sp., Lumbricus terrestris, Hirudinea class consisting of Hirudo medicinalis. The community structure of Annelida can be used as a indicator of river pollution. From the results of the study it was found that the Ancar River had experienced pollution caused by organic matter both from household waste and tofu industrial waste. Based on the BOD value it is known that station 1 is categorized as uncontaminated location, stations 2 and 4 are lightly polluted, and stations 3, 5 and 6 are moderately polluted.